ANALISIS KETERSEDIAAN AIR SAWAH TADAH HUJAN DI KELURAHAN KARYA MULIA KECAMATAN SEMATANG BORANG KOTA PALEMBANG - Fariz, Ahmad; Martini, Raden Ayu Sri; Jonizar, Jonizar; Agusri, Erny (Universitas Muhammadiyah Palembang, 2024)
Rice fields that rely mostly on rainwater for irrigation are known as rainfed rice fields. Only the wet season yields rice fields like this one. Because of the heavy rains throughout the rainy season, agricultural land's water supply is not a concern. But during the dry season, when the water supply is getting smaller, the requirement for water for plants becomes a complex issue. This study aims to find out whether the rainfall currently available can satisfy the water needs of rainfed rice fields in Karya Mulia Village, Sematang Borang District, Palembang City, and to optimize the water supply. The following was discovered by the study's findings: water balance of discharge of water availability and water requirement for rainfed rice fields in Karya Mulia Village, which has a land area of 58 Ha, there is a water balance value of 23.711 mm per hari, which meets the water balance requirement for one growing season of rice plantsIn order to be optimal in the second growing season, it can be planted with crops that balance the availability and water demand at 10.844 mm/day.